In-Vitro Study on Dissolution Profiling of Choline Chloride Encapsulated by Different Microencapsulation Technologies and Active Forms - Chauhan, Sunil Chauhan; Gautam, Bhupesh (Indian Journal of Animal Nutrition, 2020)
Â An in-vitro dissolution study was conducted to determine the effect of various microencapsulation technologies commercially employed to protect choline chloride from rumen mimic dissolution and absorption in intestinal mimic solution using two different type of actives (Liquid choline chloride 75% and choline chloride crystal 98%). This study shows that choline chloride crystals granulated by using carbohydrate matrix and coated by hydrogenated vegetable oils through top-spray fluid bed process technology have minimal dissolution of 11.14% in rumen mimic solution, liquid choline chloride granulated and further coated by hydrogenated vegetable oils through top-spray fluid bed process shows 34.71% dissolution, Liquid choline chloride absorb on silicon dioxide and coated by hydrogenated vegetable oils by pan coating shows dissolution of 82.69%, Liquid choline chloride emulsified and spray congealed shows dissolution of 84.6% while liquid choline chloride dispersed with hydrogenated vegetable oils solubilised 100% in rumen mimic solution. Results from study concluded that choline chloride active taken in crystal form granulated with cellulose based polymer and coated through fluid bed top-spray process technologies have minimal degradation in mimic rumen solution and thus maximum rumen bypass efficacy.